THE PARADIGM OF POST-SOVIET POLITICAL LEADERSHIP IN GEORGIA - CHEDIA, Beka (CENTRAL ASIA AND THE CAUCASUS, 2014)
The author analyzes the specifics of political leadership in Georgia and what people think about them, as well as the new trends that came to the fore after the 2013 presidential election, the leadership’s resources, and the ways the political community “recruits” new members. The author compares the prominent features of the presidencies between 1991 and 2014 to explain the subtleties of political leadership in Georgia. He also tries to examine why the Constitution is regularly amended to redistribute legal powers between the president and prime minister.